IJCNN'99. International Joint Conference on Neural Networks. Proceedings (Cat. No.99CH36339)
DOI: 10.1109/ijcnn.1999.836210
|View full text |Cite
|
Sign up to set email alerts
|

Phase-space based short-term load forecasting for deregulated electric power industry

Abstract: This paper describes the application of a phase-space embedding concept to artificial neural network ( A m ) based short-term electric load forecasting. Embedding parmeters for electric load time-series were determined using the method of Integral Local Deformation. In the reconstructed phase-space modular A " predictor was trained to predict loads up to jive days ahead in one-hour steps. It was found that addition of temperature and cycle variables to the phase-space based input variable set improved forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that this transformation improves the performance of the ANN (Drezga et al [21]). In the case of the day of the week and the month, each variable entered in the form of sines and cosines improves prediction (Hernández et al [15], Ramezani et al [22], Razavi and Tolson [23]).…”
Section: Data Set Amentioning
confidence: 99%
“…It has been demonstrated that this transformation improves the performance of the ANN (Drezga et al [21]). In the case of the day of the week and the month, each variable entered in the form of sines and cosines improves prediction (Hernández et al [15], Ramezani et al [22], Razavi and Tolson [23]).…”
Section: Data Set Amentioning
confidence: 99%
“…Researchers believe that electricity demand seems chaotic, many complicated facts such as temperature, price of electricity and many other factors [3][4][5][6][7][8][9] can influence electricity demand. With the power systems growth and the increase in their complexity, many factors have become influential in electric power generation and consumption.…”
Section: Introductionmentioning
confidence: 99%
“… Therefore, load forecasting is performed on the basis of previous-day hourly load curve, aggregated daily load forecast, and calendar variables (day of the week, month, etc.)  Periodic variables are supplied to the network in the form of values of sines and cosines, as it has been demonstrated that this transformation significantly improves the performance of the ANN, as shown Drezga et al [64]. Day of the week and month, which are essential for the ANN to detect weekly, monthly and seasonal patterns, are entered as sine and cosine, because the cyclical variables are best understood by ANN, as shown in [65,66].…”
Section: Artificial Neural Network Designmentioning
confidence: 99%